A University and Middle School Mentor-Scholar Partnership - Dirienzo, Denise; Ball , Scott; Proud , Robyn (Experiential Learning and Teaching in Higher Education, 2022)
The State University of New York at Oswego (SUNY Oswego) and the Oswego City School district have created a campus-community partnership through a college program that matches SUNY Oswego students as mentors with at-risk youth in grades 7 and 8 in a structured environment in the school district. The structure is academically based for college students to earn credit based on the tenets of mentoring, youth development, and relationship building. The middle school students, or “mentees” come from an at-risk background that is academic, socially, or behaviorally based. The school district recommends students for inclusion in the program. This innovative program includes a course that is rich with the pedagogy of service-learning, builds leadership characteristics and teamwork through course discussions, workshops, and the mentormentee relationship. The community benefits with increased support to at-risk students and building a pipeline between the college and K–12 community. The Mentor-Scholar Program tracks K–12 impact through state assessments, grades, social-school success outcomes, college mentors course evaluations and grades. The program tracks the impact on college students through grade assessment and reflection. The program was formed five years ago and has grown from thirty mentors with sixty mentees to 120 mentors with 300 mentees this past semester. Initial research shows an increase in attendance and GPA for K–12 students enrolled in the program and leadership skill development for college students.